A study of Chinese mobile banking users' behavioural intention to try new functions with the integrated model of UTAUT, TTF and customer service. (30th July 2021) - Wang, Shanshan
Mobile banking has been widely adopted in China. However, a lot of users just simply use it for information query or transfer and remittance. Most studies have investigated the adoption of mobile banking service, but no current study investigates users' intention to try new mobile banking functions. So, the purpose of this paper is to determine the key factors that influence consumers' intention to try new mobile banking functions. Based on the integrated model of unified theory of acceptance and use of technology (UTAUT) and task-technology fit (TTF), this study explores into the variations of the behavioural intention among different subgroups (gender, age and experience) among the Chinese mobile banking users. The results showed that task-technology fit, performance expectancy, social influence, facilitating conditions and customer service are main predictors of this behaviour intention.